ANTIOBIOTICOS NO LEITE CRU CONSUMIDO NA CIDADE DE SANTA MARIA, RS - Meller, Adalberto C.; Terra, Nelcindo N.; Brum, Marco A. R. de; Mussoi, Eurico (Revista do Centro de Ciências Rurais, 2008)
Os autores através da utilização consorciada do método bacteriológico cromatográfico, constataram a ausência de tetraciclinas e presença de penicilina em 1% das amostras de leite cru consumido na cidade de Santa Maria, RS. Abstract One hundred samples of raw liquid milk from the Santa Maria city supply were examined for the presence of penicillin and tetracycline using bacteriological and cromatographic methods. Penicillin was detected in 1% of the samples and tetracycline was absent.